To solve the equation 3q + 5 = -2q + 20, we can start by moving all the terms with q to one side of the equation. Let's add 2q to both sides:
3q + 5 + 2q = -2q + 20 + 2q
Combining like terms, we get:
5q + 5 = 20
Next, we can subtract 5 from both sides:
5q + 5 - 5 = 20 - 5
Simplifying, we have:
5q = 15
Finally, we can divide both sides by 5 to isolate q:
(5q)/5 = 15/5
Simplifying, we find:
q = 3
So the solution to the equation is q = 3.
What is the solution to the equation?
3q + 5 = –2q + 20
Question 5 options:
q = 3
q = 5
q = 15
q = 25
1 answer